Health behaviors and metabolic risk factors are associated with dyslipidemia in ethnic Miao Chinese adults: the China multi-ethnic cohort study - Fang Nie; Ziyun Wang; Qibing Zeng; Han Guan; Jingyuan Yang; Peng Luo; Lunwei Du; Junhua Wang; Feng Hong (BMC, 2021)
Abstract Background Cardiovascular risk factors in Chinese ethnic minority groups are rarely reported. Objective To quantify the cardiovascular risk factors in Miao Chinese adults and to examine the association of health behaviors and metabolic risk factors with dyslipidemia. Methods A cross-sectional analysis was conducted using baseline data from the China Multi-Ethnic Cohort (CMEC) study. A representative sample of 5559 Miao participants aged 30 to 79 years were surveyed and given physical and laboratory exams. The proportion of behavioral and metabolic risk factors were described in ethnic Miao adults. Logistic regression was utilized to evaluate the odds ratio (OR) and 95% confidence interval (CI) of the association between health behaviors and metabolic risk factors with dyslipidemia. Results In Miao Chinese adults, the prevalence of dyslipidemia was 32.8%. After multivariate adjustment, subjects with poor waist-to-hip ratio (WHR), body mass index (BMI), fasting blood glucose (FBG) and blood pressure (BP) were more likely to have higher risk of triglycerides (TG) abnormality, regardless of gender and age. Furthermore, the strongly association was detected between poor WHR and low density lipoprotein cholesterol (LDL-C) abnormality (adjusted OR = 5.24, 95%CI: 2.42-11.34) in the older subgroup (≥ 60 years). Males who current smoking were an independent risk factor only for high density lipoprotein cholesterol (HDL-C) abnormality (adjusted OR = 1.44, 95%CI: 1.05-1.99). However, in the subgroup age, current smoker were at greater risk of high TG and low HDL-C. Males with regular drinking were less likely to be high LDL-C (adjusted OR = 0.51, 95%CI: 0.32-0.81). Conclusions The present findings indicated that Miao adults with metabolic risk factors were at greater risk of dyslipidemia.